Réponses

2013-11-17T17:30:03+01:00
F(x)=(11x-x²-11-x)+(5x²+5)
      = 10x -x²-11+5x²+5
      = 10x+4x²-6
je crois
g(x)=2* (2x²+3x-2x-3) 2*(2x²+x-3) 4x²+2x-6 je crois
2013-11-17T17:32:02+01:00
F(x)= (x-1)(11-x)+5(x-1)²
tu prends le facteurs commun ici (x-1)
f(x)=(x-1)[(11-x)+5(x-1)]
     =(x-1)(11-x+5x-5)
     =(x-1)(6+4x)
     =6x+4x²-6-4x
     =4x²+2x-6     (=2(2x²+x-3))

g(x)= 2(x-1)(2x+3)
      =(2x-2)(2x+3)
      =4x²+6x-4x-6
      =4x²+2x-6     (=2(2x²+x-3))

Donc F(x)=g(x)

J'espere que c'est juste et avoir pu t'aider